Lower pole caliceal stone clearance after ESWL: the effect of infundibulopelvic angle - Lojanapiwat B. (2014)
Extracorporeal Shock Wave Lithotripsy (ESWL) represents the first choice therapy for renoureteral stone disease. Clinical controversy exists concerning the efficacy of ESWL for lower pole kidney stones. Nowadays, the factors that hinder the spontaneous passage of stone debris that results from ESWL of lower caliceal stone are the gravity-dependent position of the lower pole calices and particular features of the inferior-pole collecting system anatomy. We studied the influence of the lower infundibulo-pelvic in the success of ESWL of lower caliceal stones 10-20 millimeters in size in 50 patients with STORZ MODULITH SL-20 machine. At the mean follow-up of 6 months, only 44 per cent of the patients presenting with an infundibulo-pelvic angle of les than 90 degrees became stone free. On the other hand, 86 per cent of the patients presenting with an infundibulo-pelvic angle of greater than 90 degrees became stone free. Our data suggest that acute infundibulo-pelvic angle of the lower pole hinders the spontaneous passage of fragments after ESWL.